A study on prevalence of cognitive impairment and dementia and its associated factors among elderly patients attending outpatient clinic {KRK and/ KPP) HUSM - Kadir, Azidah Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
To detennine the prevalence of cognitive impainnent and dementia among elderly patients attending outpatients clinic HUSM